Effect of organizational commitment, job stress and work-family conflict to turnover intention - Putra, I Putu Kresna Saniscara Dewanta; Suwandana, I Gusti Made (International research journal of management, IT and social sciences, 2020)
This research was conducted in several hotels in the Kuta Badung area, Bali. The number of samples taken was 105 married female employees, using the nonprobability sampling method, specifically purposive sampling. Data collection is done through observation, interviews, and questionnaires. The analysis technique used is multiple linear regression. Based on the results of the analysis found that (1) organizational commitment has a negative and significant effect on turnover intention, so the higher organizational commitment is felt by employees, the lower the desire to leave the company, and vice versa, the lower the organizational commitment felt by employees, the higher the desire to leave the company. (2) work stress has a positive and significant effect on turnover intention, so the higher the level of work stress felt by employees, the greater the intention of employees to leave the organization. (3) work-family conflict has a positive and significant effect on turnover intention, so the higher the conflict a person feels, the higher the person's desire to leave the company.